Down-regulation of MIR-378A-3P expression associated with inflammation: The effects of restoring its levels - Seco-Cervera, Marta; Gisbert-Ferrándiz, Laura; Macias-Ceja, Dulce C.; Ortiz-Masiá, Dolores; Cosín-Roger, Jesús; Bauset, Cristina; Heras-Moran, Begoña; Navarro-Vicente, Francisco; Civera-Barrachina, Maria; Ibáñez-Cabellos, José Santiago; Calatayud, Sara; Barrachina, María D. (PloS one, 2025)
Epigenetics has emerged as a modulator of inflammation-related diseases and changes in miRNA expression have been associated with regional location, inflamed mucosa and disease activity in Crohn´s disease (CD). We analyse here the differential ileal miRNA expression in fibrotic tissue from patients with complicated CD and its relevance in inflammation and fibrosis. A miRNA sequencing analysis has been performed in ileal surgical resections from both patients with complicated CD and control subjects. The correlation analysis of data with an mRNA seq study performed in the same samples pointed to hsa-miR-378a-3p as an epigenetic regulator of inflammatory and fibrotic genes. Results demonstrate a significant diminution in the expression of miR-378a-3p in three different inflammatory conditions: ileum from complicated CD patients, intestine from DSS (Dextran Sulfate Sodium)-treated mice and macrophages polarized towards an M1 phenotype. Treatment with miR-378a-3p mimics failed to prevent inflammation and fibrosis in DSS-treated mice while it increased the expression of several cytokines and chemokines in both murine intestine and M1 macrophages. In conclusion, our study shows the downregulation of miR-378a-3p expression in human and murine intestinal inflammation and demonstrates that restoring the intestinal miR-378a-3p levels did not prevent inflammation and fibrosis in murine chronic colitis while intensified the expression of inflammatory and fibrotic markers.